Geological characteristics of early cretaceous volcanic rocks and analysis of metallogenic potential of uranium mineralization in Moganshan basin, northern Zhejiang province, China - Wang, Xiaolong; Zhang, Wengao; Cheng, Shenghong; Wang, Bo; Tang, Yifei; Li, Wei (Frontiers in Earth Science, 2024)
The Moganshan Volcanic Basin is located in the northeastern section of the Ganhang volcanic-tectonic-uranium polymetallic metallogenic belt. To explore the uranium mineralization potential of these volcanic rocks, petrographic, elemental geochemical, zircon U-Pb chronology, and Sr-Nd-Pb isotope analyses were performed on the volcanic rocks in the Moganshan Basin. The results showed that the volcanic rocks within the Moganshan Basin were formed at 130.8 ± 2.0 Ma; In addition, they are Sirich (SiO 2 content of 72.98-77.32%), alkali-rich (Na 2 O + K 2 O, with ALK values of =7.15-9.74), and potassium-rich (K 2 O/Na 2 O content of 1.41-4.34), with light rare earth elements (Rb, Th Nd, Zr, and Hf). Future more, the volcanic rocks within the Moganshan Basin are deficient in Ba, Ta, Nb, and Sr, with a negative europium anomaly (δEu of 0.10-0.17), high ISr (0.71028-0.71160), low εNd(t) values (-6.43-5.77), and other characteristics. The geological characteristics of the volcanic rocks in the Moganshan Basin are the same as those of the volcanic rocks in eastern China, and the formation age is Early Cretaceous. The formation environment is intra-land extensional and tensional. The rock-forming material primarily originates from the upper crust and has a higher average uranium content than that in the Ganhang volcanic belt. Additionally, it is speculated that the Moganshan Volcanic Basin has good potential for uranium mineralization.